Factors That Influence The Acceptance of Going Concern Audit Opinion on Manufacture Companies - Astrini Aning Widoretno (Journal of Economics, Business, and Government Challenges, 2019)
Audit opinion on a financial report is needed by users of financial statements, both external and internal parties. Users of these financial statements need opinions from independent auditors as collateral for the reliability of the information presented in the financial statements. The auditor is also obligated to evaluate wether there are doubts about the going concern of the company. The opinion about the going concern auditor’s dounts is called the going concern audit opinion. This study aims to determinde the effect of bankruptcy probability, audit lag, and company size on the acceptance of going concern audit opinion. It tested the hypotheses using the logistic regression method. The results of this study indicate that the probability of banckruptcy has a negative effect while audit lag and company size do not addect the issuance of going concern audit opinion.